Greyfriars Bobby - Atkinson, Eleanor, 1863-1942 (Salt Lake City, UT : Project Gutenberg, 2001)
"Greyfriars Bobby" by Eleanor Atkinson is a novel published in 1912 based on the true Scottish legend of a devoted dog. Written from the dog's perspective, the story follows Bobby and his deep bond with Auld Jock, a humble shepherd. When his master dies, the loyal Skye terrier faces an impossible choice between survival and devotion. Set in Edinburgh and rich with Scottish dialogue, this tale explores the extraordinary lengths of canine loyalty and captures a heartwarming chapter of Scottish folklore. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Greyfriars_Bobby_(novel)
Release date is 2001-07-01
Produced by An Anonymous Volunteeer, and David Widger
Keywords: Dogs -- Fiction; Scotland -- Fiction